An introduction to thermodynamic cycle simulations for internal combustion engines - Caton, J. A. (Jerald A.) (Chichester, West Sussex : Wiley, 2015)
This book provides an introduction to basic thermodynamic engine cycle simulations, and provides a substantial set of results. Key features includes comprehensive and detailed documentation of the mathematical foundations and solutions required for thermodynamic engine cycle simulations. The book includes a thorough presentation of results based on the second law of thermodynamics as well as results for advanced, high efficiency engines. Case studies that illustrate the use of engine cycle simulations are also provided.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Internal combustion engines -- Thermodynamics -- Computer simulation; Internal combustion engines -- Thermodynamics -- Mathematical models; TECHNOLOGY & ENGINEERING / Engineering (General); Electronic books